217k views
0 votes
-6•f (-3) - 5•g (-7) =

please help.

-6•f (-3) - 5•g (-7) = please help.-example-1

1 Answer

3 votes

Answer:

-12

Explanation:

The value of f(-3) is found by finding the point on the solid blue graph where x = -3. That point has a y-value of -3, so f(-3) = -3.

The value of g(-7) is found by finding the point on the dashed purple graph where x = -7. That point has a value of 6, so g(-7) = 6.

Putting these numbers into your expression gives ...

-6(-3) -5(6) = 18 -30 = -12

User Vinod Gubbala
by
4.5k points